Neurological manifestations associated with COVID- 19: a review - Ferreira, Yasmim Berni; Freire, Flávia Maria Ramos; Araújo, Victor Oliveira; de Oliveira, Isadora Mônica Ponte; Freitas, Lara Maria de Oliveira Paiva; dos Santos, Júlio César Claudino (Brazilian Journal of Case Reports, 2021)
The knowledge of the spinal cord irrigation is important for the therapeutic planning "COVID-19" is a potentially serious, highly transmissible infectious disease that was first identified in Wuhan, China in December 2019. Individuals infected with SARS-CoV-2 can evolve asymptomatically, with respiratory symptoms or with systemic manifestations affecting, for example, the nervous system. This review aims to discuss the neurological manifestations of SARS-CoV-2 infection, citing the prevalence of each. This study analyzed scientific articles published from 2010 to 2021 in the PubMed database. More than 35% of patients who contract the novel coronavirus develop neurological symptoms. SARS-CoV enters the brain mainly through the olfactory bulb and spreads rapidly via transneuronal route to other related areas such as cerebellum, insula, encephalon, vessels and nerves, and the brain parenchyma itself. This causes manifestations in the CNS (dizziness and ataxias), PNS (anosmia and ageusia), and the musculoskeletal system. Given existing knowledge of other coronaviruses and respiratory viruses, the wide range of CNS and PNS associations with COVID-19 is not surprising, and this is the focus of most current reports. Neurological complications, particularly encephalitis and stroke, can cause lifelong disability, requiring long-term care and substantial costs in the social and economic sphere.